Key Competencies of Managers of The Wood-Based Panels Sector in Poland- Results of Empirical Research - Małgorzata REMBIASZ; Arkadiusz BOROWIEC; Przemysław CZAJKOWSKI (Communications of International Proceedings, 2024)
The article presents the results of empirical studies conducted to identify the key competencies of managers of enterprises in the wood-based panels sector. Managerial competencies are becoming one of the key building blocks of success of the company and the development of their own people. The basis of managerial competence is being complex,  multifaceted and interdisciplinary. Other tasks and functions are performed by staff managers, line managers, leaders and managers. Managerial competencies are essential skills and traits that contribute to effective management performance and organizational competitive advantage. In the first stage of the research, a Delphi method was used to identify the 20 key competences of managers. In the second stage of the research, questionnaire surveys were conducted with a group of 89 managers employed by the seven largest companies in the wood-based panel sector in Poland. Based on the Delphi method for the key competencies of a manager , it can be stated that the most desirable of these are: responsibility, logical thinking and creativity. According to the respondents, the most important competencies of a manager are those that relate to the effectiveness of his or her work. Managerial effectiveness influences the building of a company's competitive advantage in the market. The research described in the article therefore provides a basis for further exploration of the topic.
Keywords: managerial competence; the Delphi method; corporate entrepreneurship; the wood-based panels sector